Analysis of the Machinability of Different Grades of Cast Iron - Urinov Nasillo Fayzilloevich; Saidova Mukhabbat Khamroevna; Mukhammedov Mekhriddin Beshimovich (Genius Journals, 2022)
The article discusses the problems that arise during the machining of cast iron and analyzes them
Keywords: Cast iron; lamellar graphite; ferrite; chips